VATIS update : ozone layer protection. Vol. 4, No. 107, Jul-Aug 2011 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2011)
VATIS Update Ozone Layer Protection is published 6 times a year to keep the readers up to date of most of the relevant and latest technological developments and events in the field of Ozone Layer Protection. The Update is tailored to policy-makers, industries and technology transfer intermediaries. Highlights : Carbon emissions leave climate on the brink -- Keeping vaccines cool with hydrocarbons in remote areas -- Reusable industrial degreaser -- Natural fibre-reinforced bio-foams -- New inhaler without CFC/HFA propellant -- Broad-spectrum soil fumigant THE SCIENCE OF OZONE LAYER . 4 -- WMO reports Antarctic ozone depletion for 2011 -- Carbon emissions leave climate on the brink -- Geo-engineering could help close ozone layer hole ODS PHASE-OUT IN INDIA . 5 -- Project to further the uptake of hydrocarbons -- Avoidance of HFC-134a emissions in rigid PUF manufacture -- Indian military officers visit Indonesian Halon Bank IN THE NEWS . 6 -- Iran gets help to phase out CFC-based inhalants -- India-China efforts to phase out use of CFC-based inhalers -- Inhalation spray for COPD gets FDA approval -- Philippines to phase out HCFC in the foam sector -- China secures funding for HCFC phase-out -- Viet Nam to start phasing out HCFCs in 2012 -- Fiji approves a policy on HCFC phase-out management -- European Commission bans the use of industrial gas credits REFRIGERATION/AIR-CONDITIONING . 9 -- HFO-1234yf in bus air-conditioning trial -- Keeping vaccines cool with hydrocarbons in remote areas -- Prototype R290 heat pump testing -- Energy-efficient liquid chiller -- Testing a hydrocarbon drop-in replacement for R22 in AC units -- Energy-efficient AC unit with green refrigerant -- Environment-friendly vehicle air-conditioning system SOLVENTS . 11 -- ODS-free cleaner/degreaser series -- Reusable industrial degreaser -- Airless vacuum cleaning systems -- Non-ODS solvent compositions -- Wafer-level cleaning solution -- Silicon wafer cleaning agent -- Water-based parts washing system FOAMS . 13 -- Surfactant technology for ...